Food insecurity and caregiver perceptions of food allergen risk by food purchase location in children with food allergies - Tackett, Alayna P (Transl Behav Med, 2019)
Meeting nutritional needs of children with food allergy (FA) may be challenging without affordable, quality foods. Food purchase location may impact availability of FA-safe foods; however, no research examining food purchase location in families of children with FA exists. This study compared caregiver report of food insecurity (FIS; food insecure vs. food secure), FA risk, and history of food-induced anaphylaxis (FIA) in families of children with FA, who primarily purchase food items at grocery/supermarkets (n = 140) or convenience marts/bodegas (CB; n = 32). Caregivers (N = 172; 49% mothers, 49% fathers, 2% grandparent/other relative) of children with FA (57% male; M(age) = 7.5 years; 66% White [22% Latinx and 44% non-Latinx] and 23% Black) completed an online survey. Variables included demographics, history of FIA, and caregiver perceptions of FIS and FA risk. Caregivers who purchased food items from CB versus supermarkets reported higher perceived risk of accidental ingestion (χ(2) = 20.49, p < .001, 94% vs. 50%), severe reaction (χ(2) = 15.05, p < .001, 97% vs. 61%), death (χ(2) = 27.48, p < .001, 91% vs. 49%), FIS (χ(2) = 21.69, p < .001, 94% vs. 49%), and FIA (χ(2) = 11.96, p = .001, 94% vs. 32%). Effect sizes were small–moderate (Cramer’s V = .26–.40). Families who purchased food at CB reported greater food allergen concerns and FIS than families who purchased food at supermarkets. Differences in FA-related perceived risks may reflect the health disparity and adversity these families face to meet basic nutritional needs, such as FA-related constraints. Point-of-care efforts are needed to provide early screening for families who may be at risk for experiencing FIS.